2019
DOI: 10.1371/journal.pone.0218097
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of respiratory infections among adults in Qatar (2012-2017)

Abstract: Background Limited data is available about the etiology of influenza like illnesses (ILIs) in Qatar. Objectives This study aimed at providing preliminary estimates of influenza and other respiratory infections circulating among adults in Qatar. Methods We retrospectively collected data of about 44,000 patients who visited Hamad General Hospital clinics, sentinel sites, and all primary healthcare centers in Qatar between 2012 and 2017. All sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
(58 reference statements)
3
12
0
Order By: Relevance
“…RSV and HCOV were the third most prevalent viruses detected in our hospitalized patients. In our study, RSV and FLU circulated in the same periods, owing to epidemiological interference, although the peak of RSV circulation is described as occurring earlier in other reports [14]. The general distribution of RSV positivity was similar in the different age groups (children were not present in our study population) but dyspnea was documented in 70% of people over 64 years old, in 20% of those in the range 45-64 years old and only in 10% of the younger patients (data not shown), confirming a more severe clinical impact of this infection in the elderly.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…RSV and HCOV were the third most prevalent viruses detected in our hospitalized patients. In our study, RSV and FLU circulated in the same periods, owing to epidemiological interference, although the peak of RSV circulation is described as occurring earlier in other reports [14]. The general distribution of RSV positivity was similar in the different age groups (children were not present in our study population) but dyspnea was documented in 70% of people over 64 years old, in 20% of those in the range 45-64 years old and only in 10% of the younger patients (data not shown), confirming a more severe clinical impact of this infection in the elderly.…”
Section: Discussionsupporting
confidence: 46%
“…The identified viral agents included all the respiratory viruses commonly circulating in the community as well as in the hospital setting, namely FLU A and B viruses, RHV/EV, HCOV, RSV, HMPV, PIV and ADV, as already reported by other authors [8][9][10]. It is well known that the knowledge and monitoring of the prevalence of respiratory viruses in hospital settings is very important, as the impact of these infections in hospitalized patients can have more serious consequences than in the general population [1][2][3][4][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… Lamers MM et al [ 106 ] 2015 Emerging Infectious Diseases Jordan This study characterized MERS outbreak caused viruses from Jordan and reported some deletion variants in the region. Al-Romaihi HE [ 107 ] 2019 PLOS One Qatar This report comprehensive insights and analyzed the respiratory influenza like infection from Qatar which is revealed that 0.2% cases related to MERS. Du Toit A [ 108 ] COVID-19 2020 Nature Reviews Microbiology - This research highlights provide an importance related to novel coronavirus infection and outbreak.…”
Section: Methodsmentioning
confidence: 99%
“…A comparison of xTAG RV-Fast panel, PathoFinder RF-22, CLART PneumoVir and FTD-RF-33 kits showed these assays overall sensitivities to be 72.63%, 88.42%, 63.86%, 77.89% respectively, and PPA to be 92%, 92.31%, 80.30%, 94.87% respectively [19]. A large epidemiological study in which 38,000 samples were tested for respiratory viruses by FTD-RP 21 showed its usefulness in the improvement and optimization of diagnostic procedures, as well as control and prevention of the respiratory infections [20].…”
Section: Fast Track Diagnostics Respiratory Pathogens 21/33 (Ftd-rp21 or 33)mentioning
confidence: 99%